2019
DOI: 10.1103/physrevb.100.014405
|View full text |Cite
|
Sign up to set email alerts
|

Putative spin-nematic phase in BaCdVO(PO4)2

Abstract: We report neutron scattering and AC magnetic susceptibility measurements of the 2D spin-1/2 frustrated magnet BaCdVO(PO4)2. At temperatures well below T N ≈ 1K, we show that only 34% of the spin moment orders in an up-up-down-down strip structure. Dominant magnetic diffuse scattering and comparison to published µsr measurements indicates that the remaining 66% is fluctuating. This demonstrates the presence of strong frustration, associated with competing ferromagnetic and antiferromagnetic interactions, and po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…That no magnetic structure with a different propagation vector exists in higher fields is clear from powder diffraction experiments of Ref. [12]. We thus identify the region H > H c2 as fully saturated and the field range H c1 < H < H c2 as corresponding to the potential spin-nematic phase.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…That no magnetic structure with a different propagation vector exists in higher fields is clear from powder diffraction experiments of Ref. [12]. We thus identify the region H > H c2 as fully saturated and the field range H c1 < H < H c2 as corresponding to the potential spin-nematic phase.…”
mentioning
confidence: 56%
“…The upper boundary assigned to the nematic phase in Ref. [12] does not correspond to any thermodynamic anomalies in single crystals. Counter-intuitively it moves out to higher fields with increased temperature.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We note that while this article was under review, two studies have also reported the possibility of SN order in the square-lattice frustrated ferromagnet BaCdVO(PO 4 ) 2 (29, 30).…”
mentioning
confidence: 93%
“…Indeed, in a recent theoretical and experimental investigation of the solid-solution, Sr 2 Cu(Te 1-x W x )O 6 where x = 0 and x = 1 represent Néel and columnar ordered systems, respectively, QSL signatures have been observed for the x = 0.5 compound [17]. Interestingly, the behavior exhibited by complex materials derived from the FSL, such as BaCdVO(PO 4 ) 2 [6], where signatures of a spinnematic ground state have been observed in an applied field [18,19], has further enriched the phase diagram of FSL materials, leading to new theoretical predictions [20]. By extending the J 1 −J 2 model to incorporate the effects of interplanar coupling, J 3 , magnetic ground states inaccessible to the pure FSL model can also be realized [21].…”
Section: Introductionmentioning
confidence: 99%